On the determinants of fiscal decentralization: Evidence from the EU - Francisco J. Delgado (Amfiteatru Economic Journal, 2021)
We empirically analyze the determinants of the fiscal decentralization in the European Union. Our approach consists on a quantile regression for the period 2005-2017. The results show the differences in the impact of explanatory variables on the fiscal decentralization by quantiles. Specifically, while GDP per capita or corruption are not significant in a linear modelling, both are relevant in the quantile approach with different effects along the distribution of fiscal decentralization. And other variables as population, density or inequality do not have neither the same impact among quantiles, denoting the limitations of using linear approaches for complex issues as fiscal decentralization.
Keywords: H11; H77; 330; fiscal decentralization; federalism; European Union; quantile regression